2020
DOI: 10.1021/acs.jafc.9b07290
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Yeast Peroxisomes and Cytosol Acetyl-CoA for Sesquiterpene α-Humulene Production

Abstract: Metabolic engineering of Saccharomyces cerevisiae focusing on the cytoplasm for sustainable terpenoid production is commonly practiced. However, engineering organelles for terpenoid production is rarely reported. Herein, peroxisomes, together with the cytoplasm, were engineered to boost sesquiterpene α-humulene synthesis in S. cerevisiae. The farnesyl diphosphate synthetic pathway and α-humulene synthase were successfully expressed inside yeast peroxisomes to enable high-level α-humulene production with glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 45 publications
1
53
2
Order By: Relevance
“…2A and SI Appendix, Table S2). This suggested that ClLimS was active in the peroxisome and that GPP could be translocated from the cytosol into the peroxisome, as it has previously been proposed to be the case for FPP (40,41) or other metabolites (42).…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…2A and SI Appendix, Table S2). This suggested that ClLimS was active in the peroxisome and that GPP could be translocated from the cytosol into the peroxisome, as it has previously been proposed to be the case for FPP (40,41) or other metabolites (42).…”
Section: Resultsmentioning
confidence: 58%
“…Using peroxisomal production, we achieve monoterpene production titers that were not previously possible and provide a unique example of how the yeast peroxisome can be converted into a dedicated organelle for efficient bioproduction, something that has so far been possible only for the synthesis of fatty alcohols (23,24). Although the peroxisome has previously been utilized for the production of two other isoprenoids, the sterol A B precursor squalene and the sesquiterpene α-humulene, the peroxisomal pathway alone could not outperform cytosolic production (53) and at best equaled it (41). However, in the case of squalene and α-humulene, a similar beneficial effect of establishing a peroxisomal pathway, as we observed for monoterpenes, would not be anticipated.…”
Section: Discussionmentioning
confidence: 98%
“…Peroxisome is another organelle successfully used in the production of plant natural products. After introducing the farnesyl diphosphate synthetic pathway and α-humulene synthase into the peroxisome, the production of α-humulene was increased by 2.5-fold with a titer of 1,726.78 mg/L in fedbatch fermentation (Zhang et al, 2020). By adopting the modular pathway rewiring strategy, which involved relocalization of the engineered pathway and improving the precursor supply, the titer of L-ornithine reached 1,041 mg/L (Qin et al, 2015).…”
Section: Construction Of Metabolic Compartmentalization Enriches the mentioning
confidence: 99%
“…Recently, dual engineering of metabolic pathways in the cytoplasm and organelles was performed for high-level PNPs production. Assembling the complete MVA pathway in peroxisomes or mitochondria, together with the cytoplasmic pathway, boosted the output of α-humulene ( Zhang C et al, 2020 ), and linalool ( Zhang Y et al, 2020 ), respectively.…”
Section: Optimization Of the Pathway Locationmentioning
confidence: 99%